PERGESERAN MAKNA DALAM CERPEN HACHI NO JI YAMA - Yuliani Rahmah (KIRYOKU, 2018)
(Title: Meaning Shift in Japanese Short Story “Hachi No Ji Yama”) A literary work will be translated properly according to the original text if an interpreter does the translation procedure appropriately. The translation procedure itself is divided into 14 types, but in the translation process from Japanese into Indonesian, there are three types which commonly used in procedures of the translation process.  It is  Transposition, Modulation, and Adaptation. This paper tried to explain the use of that three types of translation procedures in a Japanese short story. The short story used as the object of this paper was a children's short story entitled Hachi no Ji Yama by Tsuchida Kohei. Referring to the translation rules, the results are that the Hachi no Ji Yama short story uses 2 translation procedures, which is transposition and modulation. With the differences in the rules of language and grammatical structure between Indonesian and Japanese, the most widely used of transposition procedures are the first and second types, while the modulation used is free modulation.